Ultrasound detection of normal parathyroid glands: detection rate, topographic anatomy, and the role of underlying thyroid disease - Chiardi, Isabella; Makovac, Petra; Leoncini, Andrea; Forte, Flavio; Rotondi, Mario; Trimboli, Pierpaolo (Frontiers in Endocrinology, 2025)
IntroductionVisualizing normal parathyroid glands (PTGs) using ultrasound (US) has historically been challenging. This study aims to assess the detection rate of normal PTGs in thyroid patients and evaluate their echostructure, anatomical location and their relation with the underlying thyroid pathology.MethodsA retrospective observational study was conducted over four weeks (September–October 2024) at the Thyroid Unit of Ente Ospedaliero Cantonale (EOC). Consecutive thyroid patients undergoing US for any thyroid indication were included, while those with a history of parathyroid disease, chronic kidney disease, or recent thyroid surgery were excluded. The primary outcome was the detection rate of normal PTGs. Secondary outcomes included PTG echostructure, anatomical location, and correlations with patient characteristics (age, gender, BMI, thyroid volume, and underlying thyroid pathology).ResultsNormal PTGs were identified in 45.1% of patients (n=51). Most PTGs were located near the lower pole of the thyroid lobes and appeared mildly hyperechoic. Thyroid volume was inversely associated with PTG detection (p=0.001), while underlying thyroid pathology (e.g., thyroiditis, nodular disease) had no significant impact on detection rates.ConclusionNormal PTGs can be visualized using US, particularly near the lower thyroid poles. Detection rates decrease in patients with larger thyroid volumes or athyreotic status. These findings confirm and expand on recent studies, challenging the historical belief that normal PTGs are undetectable, with potential implications for endocrine imaging and surgical planning.